2012
DOI: 10.4172/2161-0444.1000119
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Clove Tea (Syzygium Aromaticum) on Body Weight and Biochemical Parameters of Rats Subjected to Ethanol Consumption and Abstinence

Abstract: Clove has a large number of therapeutic properties and its tea has been used by the general population as antiinflammatory, antihyperglycemic, antimutagenic, bactericidal, and nematicidal, among others. Thus, the aim of this study was to assess the effect of clove on biochemical parameters of rats subjected to ethanol consumption and abstinence. The animals were subjected to ethanol intake before and after treatment with clove tea, according to their groups, as follows: GW received water (control); GE received… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…Pepper is insoluble in water and should thus be used as a spice to be sprinkled over food; however, cloves, mint, and parsley can be brewed in a tea. [62][63][64]…”
Section: Discussionmentioning
confidence: 99%
“…Pepper is insoluble in water and should thus be used as a spice to be sprinkled over food; however, cloves, mint, and parsley can be brewed in a tea. [62][63][64]…”
Section: Discussionmentioning
confidence: 99%
“…and Perry (Myrtaceae), is used as a topical application to relieve pain and to promote healing (Chaieb et al, 2007). Previous research has shown that clove has several therapeutic properties, such as antiinflammatory, neuroprotective action, antihyperglycemic, nervous stimulant, tonic antimutagenic, aphrodisiac, bactericidal, nematicidal, fungicide, anti-toothache, antioxidant, analgesic, anesthetic and hypotensive properties (Mani et al, 2012;Dashti-R et Morshedi, 2009). Several works have demonstrated that the major component of the essential oil of Syzygium aromaticum is eugenol and lesser amounts of beta-caryophyllene and eugenol acetate (Chaieb et al, 2007;Prashar et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Nada, (2011)showed that rats treated with clove oil before and after whole body gamma irradiation exhibited significant amelioration in liver marker enzymes (AST, and ALT). Mani et al,(2012) found that consumption of clove tea before or after ethanol administration had a good effects on liver enzymes in rats, so they suggested that prolonged ethanol intake should be avoided when clove tea is consumed daily in a moderate amount.…”
Section: Serum Total Cholesterol and Triglycerides (Mg\dl)of Diabetic Rats And Consumed Syzygiumaromaticummentioning
confidence: 99%